The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/00031348221091948
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Cancer Screenings, Diagnoses, and Mortalities During the COVID-19 Pandemic: Implications and Future Recommendations

Abstract: Introduction The impact of the COVID-19 pandemic on cancer screenings and care has yet to be determined. This study aims to investigate the screening, diagnosis, and mortality rates of the top five leading causes of cancer mortality in the United States from 2019 to 2021 to determine the potential impact of the COVID-19 pandemic on cancer care. Methods A retrospective cohort study investigating the impact of the COVID-19 pandemic on screening, diagnoses, and mortality rates of the top five leading causes of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 28 publications
1
17
2
Order By: Relevance
“…Some studies proposed that the COVID-19 could impair the prognoses of pancreatic cancer patients, 21,22 which probably resulted from the impaired cancer screening, diagnosis, and care. 23 The vaccination was not discovered associated with the OS of PAC patients. However, with further interaction analyses, vaccination was observed to have interacted with the adjuvant chemotherapy administration.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Some studies proposed that the COVID-19 could impair the prognoses of pancreatic cancer patients, 21,22 which probably resulted from the impaired cancer screening, diagnosis, and care. 23 The vaccination was not discovered associated with the OS of PAC patients. However, with further interaction analyses, vaccination was observed to have interacted with the adjuvant chemotherapy administration.…”
Section: Discussionmentioning
confidence: 96%
“…24 Third, the unvaccinated patients worried about the infection of COVID-19 and were thereby less likely to visit the hospital and receive the medical treatments. 23 Some limitations of the study should be emphasized. First, it is a retrospective study with a certain uncorrected bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another inquiry in the UK conducted by Maringe and colleagues (24) indicated that the COVID-19 pandemic leveraged the number of deaths within five years after diagnosis by 4.8-16.6% for esophageal, lung, colorectal, and breast cancer. According to Concepcion et al's (25) study, between 2019 and 2020 in the U.S., cancer screening for breast cancer diminished by 16.01% and for colorectal cancer by 24.98%. These reduced cancer screenings might contribute to a rise by 2.89% for breast cancer and a rise by 19.72% for colorectal cancer as well as a rise in the number of breast and colorectal cancer deaths between 2019 to 2021 in the U.S (25).…”
Section: Long-term Impacts Of Reduced Cancer Screeningmentioning
confidence: 99%
“…According to Concepcion et al's (25) study, between 2019 and 2020 in the U.S., cancer screening for breast cancer diminished by 16.01% and for colorectal cancer by 24.98%. These reduced cancer screenings might contribute to a rise by 2.89% for breast cancer and a rise by 19.72% for colorectal cancer as well as a rise in the number of breast and colorectal cancer deaths between 2019 to 2021 in the U.S (25).…”
Section: Long-term Impacts Of Reduced Cancer Screeningmentioning
confidence: 99%